Teacher and Student Empowerment of SMKN 3 Pahunga Lodu through Making Seaweed Sticks (Eucheuma cottonii) - Nurbety Tarigan; Yatris Rambu Tega; Firat Meiyasa; Suryaningsih Ndahawali; Krisman Umbu Henggu; Lusianus Heronimus Sinyo Kelen (MITRA: Jurnal Pemberdayaan Masyarakat, 2021)
Seaweed-based processed products are still very limited in the East Sumba Regency despite the abundance and availability of seaweed (Eucheuma cottonii). Therefore, diversification of seaweedbased processed products is necessary. One such product is seaweed sticks. This activity was carried out at SMK Negeri 3 (SMKN 3) Pahunga Lodu, East Sumba Regency. The activity targeted teachers and students majoring in seaweed processing, agribusiness, and seaweed cultivation. The purpose of this activity was to empower teachers and students to produce seaweed-based products. The activities included a workshop, seaweed stick making, and mentoring. The workshop materials covered information on the nutritional content of seaweed and how seaweed sticks are made. The workshop was followed by implementing what was taught in the workshop by making the seaweed sticks. Then, mentoring was provided for three consecutive weeks. The result of this program is that the participants gained knowledge on how seaweed is processed into sticks. During the first week of mentoring, the participants produced 50 packages of 100 gr sticks, 29 packages of 80 gr sticks, and 3 jars of 120 gr sticks. In the second week, they managed to produce 89 packages of 100 gr sticks. On the third week and fourth weeks, 101 packages of 100 gr sticks and 70 packages of 100 gr sticks were produced, respectively. This shows that the participants were enthusiastic about producing and selling seaweed sticks. It is hoped that the participants will produce seaweed sticks continuously.